Elucidating the interaction of ticlopidine with serum albumin and its role in bilirubin displacement in vitro. Issue 4 (4th March 2019) - Afrin, Shumaila; Rahman, Yusra; Tabish, Mohammad
Abstract : Ticlopidine is an anti-platelet drug that functions as a P2Y12 receptor antagonist. The present study provides a detailed characterization of interaction of ticlopidine with a model transport protein, bovine serum albumin (BSA) as well as an assessment of its bilirubin displacing ability using a multi-spectroscopic approach in combination with isothermal titration calorimetry. The value of binding constant determined using ITC studies was found to be 3.03 × 10 3 M −1 with a binding stoichiometry of approximately 1:1. Competitive site marker experiments indicate that ticlopidine binds to Sudlow site I, located in subdomain IIA of BSA. In addition, Circular dichroism and 3D fluorescence spectroscopy indicated structural and conformational changes in BSA on interaction with ticlopidine. Thermodynamic parameters suggested that the reaction was spontaneous, exothermic, entropically driven, and involved hydrophobic interactions. These results were well supported by those obtained through molecular docking studies. Additionally, the effect of ticlopidine on bilirubin and albumin interaction was evaluated using the peroxidase method as well as through fluorescence spectroscopy. Ticlopidine was found to displace bilirubin from serum albumin. Moreover, the binding constant of bilirubin–serum albumin interaction also decreased in presence of ticlopidine. The results indicated that ticlopidine is a competitive displacer of bilirubin in vitro and may contribute to the incidences hyperbilirubinemia associated with the usage of this drug.